Rules and Regulations for the Investment Account. (Policy Papers; Policy Paper, 2018)
The objective of the Investment Account (IA) is to provide a vehicle for the investment of a part of the Fund's assets so as to generate income that may be used to meet the expenses of conducting the business of the Fund. Achieving this objective would help diversify the sources and increase the level of the Fund's income, thereby strengthening its finances over time.